2007
DOI: 10.2214/ajr.07.2254
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Percutaneous Needle Lavage in Calcific Tendinitis of the Shoulder: Short- and Long-Term Results

Abstract: Percutaneous needle aspiration and lavage is effective in the short term and in the long term in calcific tendinitis of the shoulder, with results similar to or better than those published for other techniques, and it is only slightly invasive and painful. Progress after treatment may include a transitory period of recurrence of the pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
2
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 24 publications
(57 reference statements)
11
120
2
5
Order By: Relevance
“…1). This technique, which in past years was performed under fluoroscopic guidance, can significantly reduce the volume of calcifications and produce functional and clinical improvement [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…1). This technique, which in past years was performed under fluoroscopic guidance, can significantly reduce the volume of calcifications and produce functional and clinical improvement [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…10,12 Percutaneous treatment is not indicated if the calcification is asymptomatic, is very small (,5 mm), has migrated into the bursal space or is eroding the humeral cortical bone. 26 Since the first study performed by Farin et al, different techniques and approaches have been reported in the literature 12,15,17,23,27,28 using one or two needles of different sizes to remove calcium. To date, no evidence exists in favour of using a specific size or number of needles.…”
Section: Treatment Of Calcific Tendinopathy Of the Rotator Cuffmentioning
confidence: 99%
“…These techniques may utilize two needles 24,41,42 or one. [43][44][45][46][47][48] The technique is often performed as follows ( Fig. 3 and 4 At that point, the needle is either drawn back into the subacromial bursa, or is completely withdrawn and a new needle is inserted into the subacromial bursa.…”
Section: Injectionsmentioning
confidence: 99%
“…47 The ability to remove more calcium during the procedure does not result in better pain relief 42 and a decrease in calcium deposit size is seen regardless of initial ability to remove all calcium from the deposit. 43,45 Removal of calcium may not even be necessary to provide pain relief. 52 …”
Section: Injectionsmentioning
confidence: 99%